Distribution of Porphyromonas gingivalis fimA genotypes in patients affected by rheumatoid arthritis and periodontitis - Ayala Herrera, Jose Luis (2018)
OBJECTIVE: To determine and compare the distribution of Porphyromonas gingivalis fimA genotypes in patients affected by Rheumatoid arthritis (RA) and periodontitis (PE).